2010
DOI: 10.1097/rlu.0b013e3181ef0b1b
|View full text |Cite
|
Sign up to set email alerts
|

Cervical and Uterine Metastasis From Carcinoma of Breast Diagnosed by PET/CT

Abstract: A 44-year-old apparently healthy woman presented with a 5-month history of intermittent vaginal bleeding. Clinical examination raised the suspicion of cervical neoplasia which was confirmed to be a metastatic adenocarcinoma on subsequent histopathological evaluation. An F-18 FDG PET/CT scan performed soon after revealed increased uptake in the cervix, extending upwards into the endometrial cavity. Additionally, small FDG avid spiculated soft tissue density masses were visualized in bilateral breast parenchyma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A comprehensive literature review performed by Huo et al identified 13 cases of breast metastasis to the endometrium between 1984 and 2015, demonstrating that ER/PR-positive tumors, especially from lobular type (ILC), were more likely to result in endometrial metastasis in comparison to IDC [ 5 , 6 ]. Most of these uterine metastases were detected in known cases of breast cancer patients during their follow-up and hormone therapy period, and in 2016 Cift et al reported a known case of ductal breast carcinoma under tamoxifen therapy who had myometrial metastasis [ 1 , 6 8 , 11 , 13 , 14 ]; there was only 1 patient in Delhi who had no prior history of cancer [ 15 ] such as ours, which might be due to poor compliance of cancer screening programs in both countries (India and Iran).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive literature review performed by Huo et al identified 13 cases of breast metastasis to the endometrium between 1984 and 2015, demonstrating that ER/PR-positive tumors, especially from lobular type (ILC), were more likely to result in endometrial metastasis in comparison to IDC [ 5 , 6 ]. Most of these uterine metastases were detected in known cases of breast cancer patients during their follow-up and hormone therapy period, and in 2016 Cift et al reported a known case of ductal breast carcinoma under tamoxifen therapy who had myometrial metastasis [ 1 , 6 8 , 11 , 13 , 14 ]; there was only 1 patient in Delhi who had no prior history of cancer [ 15 ] such as ours, which might be due to poor compliance of cancer screening programs in both countries (India and Iran).…”
Section: Discussionmentioning
confidence: 99%